Correlations of multiscale structural evolution and homogeneous flows in metallic glass ribbons - Jiacheng Ge; Peng Luo; Zhenduo Wu; Wentao Zhang; Sinan Liu; Si Lan; Jonathan D. Almer; Yang Ren; Xun-Li Wang; Weihua Wang (Materials Research Letters, 2023)
Studying the flow behavior is critical to understand the deformation mechanism of amorphous solids. However, detecting the basic flow events in amorphous solids is challenging. Here, by simultaneous SAXS/WAXS, elementary flow carriers in wound metallic glasses are identified from flow-induced structural heterogeneities with a radius of gyration of 2.5∼3.5 nm. Their size increases and morphology changes from sphere-like to rod-like under flow. Moreover, the atomic structure exhibits an unusual change to a more disordered state during winding/annealing at the temperature of ∼0.8 Tg. This work provides an atomic-to-nanoscale description of the flow carriers of amorphous solids during deformation.Impact StatementThe elementary flow carriers in metallic glasses have a radius of gyration of 2.5∼3.5 nm. During flow, their size increases and morphology changes from sphere-like to rod-like.